Finite and non-finite verbs in political news: Israeli and Palestinians issues - Yoshua Hardjoni Gani; Beny Alam; Winda Lutfiyanti (LADU: Journal of Languages and Education, 2020)
Background: For centuries, newspapers have delivered news to the reading public informing important events of a day. Specifically, the political news nowadays is more relaxed and popular than other sections, not to mention that it is also presented in an interesting and serious manner. Purpose: This research aims to classify and determine the verbs whether they are finite or non-finite. Design and methods: The subjects of the research are political news of “The Jakarta Post” newspaper which have taken and collected from two articles published on Monday, January 27th, 2020 and Tuesday, January 28th, 2020, with the focus on news related to “Donald Trump’s issues between Israeli and Palestinians”. The method used in the research is descriptive qualitative methodology. The main theory of this research are Greenbaum and Nelson (2009), Burton-Roberts (2011), and Lobeck and Denham (2014). The steps in analyzing the data include: (1) collecting the data, (2) categorizing the collected data into their own classifications, (3) analyzing the data, (4) determining the data whether they are finite or non-finite verbs, and finally (5) concluding the data. Results: The results of the research shows that from the total of two hundred and seventy two findings, there are one hundred and twenty-eight data of finite verbs (47%) and one hundred and forty-four data of non-finite verbs which then are divided into thirty-one –to infinitives (12%), twenty-six bare infinitives (10%), twenty-three passive participles (8%), thirty –ing participles (11%), twelve passive participle forms of be (4%), nine progressive participle forms of be (3%), and thirteen perfect participle forms of have (5%).